2019
DOI: 10.1093/brain/awz269
|View full text |Cite
|
Sign up to set email alerts
|

Interictal epileptiform discharges shape large-scale intercortical communication

Abstract: Focal epilepsy is associated with large-scale brain dysfunction. Dahal et al. reveal that interictal epileptiform discharges modulate normal brain rhythms in regions beyond the epileptic network, potentially impairing processes that rely heavily upon intercortical communication, such as cognition and memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 59 publications
5
59
0
Order By: Relevance
“…We detected spindle band oscillations, which were present in pups of all ages, to facilitate comparisons. We quantified spatial extent using the two-dimensional organization of the NeuroGrid to determine the proportion of electrodes expressing co-occurring spindle band oscillations with a reference electrode located in primary somatosensory cortex ( Figure 3A) (42). Waveform was characterized using an asymmetry index ( Figure 3B) and power was extracted from the filtered Hilbert envelope ( Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…We detected spindle band oscillations, which were present in pups of all ages, to facilitate comparisons. We quantified spatial extent using the two-dimensional organization of the NeuroGrid to determine the proportion of electrodes expressing co-occurring spindle band oscillations with a reference electrode located in primary somatosensory cortex ( Figure 3A) (42). Waveform was characterized using an asymmetry index ( Figure 3B) and power was extracted from the filtered Hilbert envelope ( Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Gelinas et al 83 showed that hippocampal interictal spikes induced spindle generation in frontal region during NREM sleep but also during REM sleep and wakefulness, suggesting that hippocampal spikes produce changes in sleep architecture across large networks involved in normal sleep. The same group also showed that the dynamic oscillatory coupling between interictal epileptic discharges and sleep spindles induces network alteration outside the EZ 84 …”
Section: Sleep and Alfmentioning
confidence: 96%
“…The same group also showed that the dynamic oscillatory coupling between interictal epileptic discharges and sleep spindles induces network alteration outside the EZ. 84…”
Section: Insight From Intracranial Electroencephalographic Recordingsmentioning
confidence: 99%
“…By extension, IEDs could conceivably disrupt the organization and functioning of WM networks. Indeed, large-scale network changes precede ( Ibrahim et al, 2014 ) and follow IEDs ( Lengler et al, 2007 ; Ibrahim et al, 2014 ; Dahal et al, 2019 ). Moreover, the vulnerability of network topologies to IEDs has previously been associated with worse neurocognitive outcomes ( Ibrahim et al, 2014 ).…”
Section: Pathophysiological Mechanisms Of Wm Impairment In Epilepsymentioning
confidence: 99%